P023 PATIENT AND HEALTHCARE PROFESSIONAL VIEWS ON EMOTIONAL HEALTH AND INTIMACY IN ULCERATIVE COLITIS: RESULTS OF A GLOBAL ULCERATIVE COLITIS NARRATIVE SURVEY. (7th February 2019) - Schreiber, Stefan; Panaccione, Remo; Kayhan, Cem; Lopez-Sanroman, Antonio; Peyrin-Biroulet, Laurent; Armuzzi, Alessandro; Dubinsky, Marla; Melmed, Gil; Rubin, Michele; Connor, Susan; Keefer, Laurie; Rubin, David T
Abstract: Objective: The Ulcerative Colitis (UC) Narrative is a global survey of patients (pts) and gastroenterology physicians (GIs) aimed at identifying the impact of the disease and comparing and contrasting perceptions of UC burden and management approaches. Here, we present data from 2100 pts and 1254 GIs in Australia, Canada, Finland, France, Germany, Italy, Japan, Spain, the UK, and the USA, with a focus on emotional health and intimacy in the care of pts with UC. Methods: Surveys were conducted online and by phone by The Harris Poll between August 2017 and February 2018. Eligible adult pts with UC (endoscopy confirmed) were those who had visited a GI in the previous 12 months and had ever received prescription medication for UC. Self-reported medication history was used as a proxy for disease severity, with pts with moderate to severe UC defined as pts who had ever taken immunosuppressants, tumor necrosis factor inhibitors, other biologics, or corticosteroids for >4 of the past 12 months. Pts who had only ever taken 5-aminosalicylates or had a colectomy were excluded. Eligible GIs were those who saw ≥10 UC pts each month (≥5 in Japan), of whom ≥10% were taking a biologic and did not practice in a long-term care facility or hospice. Data are presented from all respondents who consented and completed the survey. Results: Mean pt age was 40.8 (standard deviation [SD] 12.4) years and 82% of pts had moderate to severe UC. Although only 21% and 15% of pts had ever been diagnosed with anxiety or depression, respectively, 7% were seeing a psychiatrist, psychologist, or therapist as part of their UC management. The majority of pts (84%) found UC mentally exhausting, even pts whose UC was not moderate to severe (75%) or pts whose UC was controlled with few to no symptoms (82%). Discussing the emotional impact of UC during routine appointments was less of a priority for GIs compared with pts (7% of GIs considered it one of their top three priorities vs 13% of pts). Only 45% of pts felt comfortable discussing sex life and personal relationship concerns with their GI. Three in ten pts (30%) wished their GIs better understood the effect of UC on their mental health, whereas only 40% of pts (and 44% of GIs) considered managing the psychological impact of UC to be important in managing UC. Only half of pts (52%) felt comfortable discussing emotional concerns with their GI; however, only 23% of GIs regularly discussed the impact of UC on mental and emotional health with pts. Conclusion: Emotional and mental health issues are infrequently discussed at routine appointments. This suggests that mental health concerns are often not covered during appointments, despite most pts reporting UC as a mentally exhausting condition. The mental burden and exhaustion of UC should not be underestimated and GIs need to initiate these discussions during consultations.